(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
During the sixteenth and seventeenth centuries about 85 per cent of the population of India lived in its villages. Both peasants and landed elites were involved in agricultural production and claimed rights to a share of the produce. This created relationships of cooperation, competition and conflict among them. The sum of these agrarian relationships made up rural society. At the same time agencies from outside also entered into the rural world. Most important among these was the Mughal state, which derived the bulk of its income from agricultural production. Agents of the state – revenue assessors, collectors, record keepers – sought to control rural society so as to ensure that cultivation took place and the state got its regular share of taxes from the produce. Since many crops were grown for sale, trade, money and markets entered the villages and linked the agricultural areas with the towns.